Boolean functions with small spectral norm, revisited - Sanders, T (Cambridge University Press, 2018)
We show that if f is a Boolean function on Fn 2 with spectral norm at most M then there is some L exp(M3+o(1) ) and subspaces V1,..., VL such that f = i ±1Vi .